Beyond the Concepts of the Secular and the Religious - Smith, Brent A. (Cultural and religious studies, 2016)
The U.S. Supreme Court gave the privately owned company Hobby Lobby the authority to deny healthcare coverage to its employees, a decision by a secular authority involving the owner’s religious beliefs. In France, the first issue released by the secular magazine Charlie Hebdo after the terrorist attack depicted a religious figure declaring, "All is forgiven." In each instance the boundaries between the "secular" and "religious" were transgressed. In the academic study of religion, an additional direction methodology needs to take involves the lens formed by academic concepts and categories as shaped by the historical development of the university’s discourses and lines of inquiry. The university is an epistemological project and we look "out there" through concepts and categories formed "in here", inside of the history of "the university". It is another dimension to the problem of the insider/outsider. This paper will use the characteristics of interdisciplinarity to historicize how the university as an epistemological project has developed the concepts of "religion", the "secular", and the binary they form, in order to suggest directions for their use to interpret events in the 21st century through the academic study of religion.